Solution focused therapy. (SAGE video tutorials., 2015)
Dr. Tina Rae, a Senior Lecturer at the University of East London, focuses on the benefits of Solution-Focused Brief Therapy as it is applied with children and young people. She elaborates on the importance of this constructionist approach for teachers and counsellors.